Recyclable and self-healable elastomers with high mechanical performance enabled by hydrogen-bonded rigid structure. (3rd January 2023) - Hou, Yujia; Xu, Hu; Peng, Yan; Xiong, Hui; Cai, Minjie; Wen, Yong; Wu, Qi; Wu, Jinrong
Abstract: It is a challenge to develop high-performance elastomers while maintaining good recyclability and self-healable ability. Here, we synthesis the recyclable and self-healable elastomers with excellent overall mechanical properties by introducing rigid structures (benzoic acid groups and imidazole groups) into the side chains of the acrylate polymer. By virtue of the rigid structures, the mechanical performance of the elastomers is greatly improved. Further, reversible hydrogen bonds can be formed between the rigid structures, endowing the network structures with good dynamics and providing elastomers with superior capability of recycling and self-healing. As a result, the elastomers reach the strength of 20.4 MPa, Young's modulus of 79 MPa, toughness of 72 MJ/m 3 and self-healing efficiency up to 98%. Besides, the samples after three times of recycling can still keep great mechanical properties. Graphical abstract: Image 1 Highlights: An ingenious strategy is proposed to develop recyclable and self-healable elastomers with high mechanical performance. The mechanical properties of the elastomers are greatly improved via the unique hydrogen-bonded rigid structure. Hydrogen bonds between rigid structures endow elastomers with good capability of recycling and self-healing. The elastomers reach high strength of 20.4 MPa, Young's modulus of 79 MPa and toughness of 72 MJ/m 3 .